Mineralization of the Callorhinchus Vertebral Column (Holocephali; Chondrichthyes) - Pears, Jacob B.; Johanson, Zerina; Trinajstic, Kate; Dean, Mason N.; Boisvert, Catherine A. (Frontiers in Genetics, 2020)
Members of the Chondrichthyes (Elasmobranchii and Holocephali) are distinguished by their largely cartilaginous endoskeletons, which comprise an uncalcified core overlain by a mineralised layer; in the Elasmobranchii (sharks, skates, rays) most of this mineralisation takes the form of calcified polygonal tiles known as tesserae. In recent years, these skeletal tissues have been described in ever increasing detail in sharks and rays, but those of Holocephali (chimaeroids) have been less well-studied, with conflicting accounts as to whether or not tesserae are present. During embryonic ontogeny in holocephalans, cervical vertebrae fuse to form a structure called the synarcual. The synarcual mineralises early and progressively, anteroposteriorly and dorsoventrally, and therefore presents a good skeletal structure in which to observe mineralised tissues in this group. Here, we describe the development and mineralisation of the synarcual in an adult and stage 36 elephant shark embryo (Callorhinchus milii). Small, discrete, but irregular blocks of cortical mineralisation are present in stage 36, similar to what has been described recently in embryos of other chimaeroid taxa such as Hydrolagus, while in Callorhinchus adults, the blocks of mineralisation are more irregular, but remain small. This differs from fossil members of the holocephalan crown group (Edaphodon), as well as from stem group holocephalans (e.g., Symmorida, Helodus, Iniopterygiformes), where tesserae are notably larger than in Callorhinchus and show similarities to elasmobranch tesserae, for example with respect to polygonal shape.